MENINGKATKAN KETERAMPILAN KERJASAMA DAN INTERAKSI SOSIAL ANAK MELALUI PERMAINAN TRADISIONAL CUK-CUK BIMBI PADA ANAK USIA 5-6 TAHUN DI TK PERTIWI RANTING MARTAPURA - isnaniah; Nisa, Uswatun; yusuf , Muhammad; Baiti , Noor (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Cooperation and social interaction are essential aspects of early childhood social development that should be fostered through developmentally appropriate learning activities. This study aimed to improve the cooperation and social interaction skills of Group B kindergarten children through the implementation of the traditional game Cuk-Cuk Bimbi at TK Pertiwi Ranting Martapura. The study employed a Classroom Action Research (CAR) design conducted in two cycles, each consisting of planning, action, observation, and reflection. The participants were 15 children aged 5–6 years. Data were collected through observation and analyzed using descriptive quantitative analysis. The findings revealed that the implementation of the traditional game Cuk-Cuk Bimbi gradually improved children's cooperation and social interaction skills across each cycle. The percentage of children achieving the Developing as Expected (BSH) and Very Well Developed (BSB) categories increased from 33.3% in Cycle I Meeting 1 to 53.3% in Cycle I Meeting 2, then to 86.6% in Cycle II Meeting 1, and finally reached 100% in Cycle II Meeting 2. These findings indicate that the traditional game Cuk-Cuk Bimbi, supported by teacher scaffolding, is effective in improving young children's cooperation and social interaction through interactive, enjoyable, and child-centered learning activities.